Litchi-shaped polyacrylamide microspheres and preparation method and application thereof
By using lychee-like polyacrylamide microspheres as deep-dip regulators in the oil field, the problems of water injection and small volume and low recovery in the prior art are solved, and the degree of oil use and recovery rate in the medium and low permeability layers are improved, and economic costs and environmental pollution are reduced.
Patent Information
- Application Number
- CN202411556200.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the process of water flooding development in the oil field, it is difficult to effectively expand the water injection wave and volume and improve the recovery rate, especially in the low degree of oil use in the medium and low permeability layers, which aggravates the reservoir heterogeneity and increases economic costs and environmental pollution.
Litchi polyacrylamide microspheres are used as deep-dip generators, and microspheres with litchi-like morphology are formed by embedding copper oxide quantum dots on mesoporous microspheres and adding components such as azo initiators to the polymerization reaction. This microsphere can play an excellent deep-driving role in low-permeability reservoirs with high temperature and high mineralization.
Lychee-like polyacrylamide microspheres can effectively enter the deep layer of the formation, block the pore throat after absorbing water and expanding, improve the fluid flow ratio, expand the water injection wave and volume, improve the recovery rate of crude oil, reduce the filling cost, and avoid expansion and rupture after absorbing water.
Smart Images

Figure CN119060275B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petrochemical industry, and particularly relates to litchi-shaped polyacrylamide microspheres and a preparation method and application thereof. Background Art
[0002] The ultimate recovery of the reservoir is affected by the volume of water injection and the oil recovery efficiency. Long-term water flooding development exacerbates the heterogeneity of the reservoir, forming large pores in the oil layer, causing a "short circuit" in the water flooding. Therefore, in order to stabilize the production of oil fields and improve the economic development benefits of oil fields, it is an important means to improve the oil recovery effect by using deep flooding technology to improve the heterogeneity between and within layers, expand the volume of water injection, and change the mobility ratio between the displacement fluid and the displaced fluid.
[0003] The deep displacement technology is essentially a branch of the chemical profile control technology of water injection wells, which includes shallow adjustment, deep profile control and deep displacement. Shallow adjustment generally uses a profile control agent with a relatively high strength to plug the main water-absorbing layer, control the increase in water content, and improve the utilization of the poor oil layer. For oil reservoirs with serious intra-layer contradictions, shallow adjustment can only form a plug in the high permeability zone near the well. When the injected water exceeds the plugging position of the profile control agent and enters the low permeability zone, if there is no interlayer between the high and low permeability layers, the injected water will go back to the high permeability layer and advance along the high permeability layer. Therefore, shallow adjustment has a very limited effect on expanding the sweep coefficient of injected water and improving the recovery rate.
[0004] So far, water injection development adopted by most oil fields has several advantages: replenishing formation energy; maintaining oil layer pressure to stabilize oil reservoir production; simple process, easy to adjust; low cost, good economic benefits. However, in the middle and late stages of oil field exploitation, large-scale and long-term water injection development has aggravated the horizontal and vertical heterogeneity of the reservoir, causing the injected water to advance or finger-step along the channels or cracks with the least resistance between layers, resulting in the high permeability layer between the injection and production wells being flooded prematurely, while the degree of influence of the medium and low permeability layers is reduced, resulting in the water drive effect not being obvious in the medium and low permeability layers, so that the oil in the medium and low permeability layers is low in utilization, or even cannot be exploited, and increasing economic costs and environmental pollution.
[0005] The effective period of deep profile control agent for plugging pores is related to many factors: the matching ability of profile control agent and pores, the heat resistance of profile control agent itself and reservoir channeling, etc. The polymer microsphere deep profile control agent has the characteristics of "entering, blocking and moving". While achieving deep profile control, it continuously redistributes the profile control agent, increases the profile control radius, increases the scanning area of injected water, and achieves the purpose of fluid diversion in the deep oil layer. At the same time, polymer microsphere profile control agent can improve the fluid mobility ratio and move like a piston in the formation, thereby achieving the purpose of oil displacement.
[0006] Quantum dots are a new type of semiconductor nanomaterial, a type of semiconductor nanoparticle composed of II-VI or III-V elements with a radius smaller than or close to the exciton Bohr radius. Due to the influence of quantum size effect and dielectric confinement effect, quantum dots have unique properties, which makes quantum dots have great application potential in the fields of oil extraction and catalysis. The prior art generally directly uses quantum dots as tracers or oil displacement agents, and the application range is relatively narrow. CN115306362A directly uses quantum dots as oil displacement agents, and uses the extremely strong penetration and oil washing effects of quantum dots to penetrate into the rock surface to remove the oil film and improve the oil washing efficiency; however, its cost is relatively high, and it does not have the effect of blocking and regulating displacement. CN115181217A prepares core-shell microspheres with fluorescent tracing function, by introducing fluorescent quantum dots in the process of preparing the core microsphere solution, and then mixing and adsorbing with the shell monomer water to prepare the core-shell microsphere solution. The fluorescent quantum dots are located inside the core-shell fluorescent microspheres and will not detach, thereby improving the subsequent detection accuracy. The quantum dot microspheres are prepared into microspheres of ordinary morphology by direct in-situ polymerization process, and only the tracer function of quantum dots is used for detection, and the plugging and flooding effect is limited. The fluorescent microspheres prepared by CN117736722A, CN115247060A, etc. have smooth surfaces and cannot be used as flooding agents. Summary of the invention
[0007] The present invention proposes a litchi-shaped polyacrylamide microsphere and a preparation method and application thereof. The polyacrylamide microsphere with a specific morphology can still play an excellent deep adjustment and displacement role in a high-temperature, high-mineralization low-permeability oil reservoir, greatly reducing the injection cost and improving the recovery rate. The litchi-shaped polyacrylamide microsphere prepared by the present invention has a small particle size, which is smaller than the size of the formation pore throat, and can smoothly enter the deep formation, block the pore throat after absorbing water and swelling, redirect the liquid flow, expand the swept volume, and thus improve the recovery rate of crude oil.
[0008] The present invention provides a method for preparing litchi-shaped polyacrylamide microspheres, comprising the following steps:
[0009] (1) treating the mesoporous microspheres with a mercaptosilane coupling agent to obtain mercapto-modified mesoporous microspheres;
[0010] (2) adding thiolated mesoporous microspheres to a copper oxide quantum dot solution, uniformly dispersing by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:(0.01-0.1);
[0011] (3) Firstly, an azo initiator is dispersed in an organic solvent, and then the mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0012] (4) Add acrylamide and acrylic acid monomers, a crosslinking agent, and a surfactant to the premixed solution and stir evenly; react at 50-70°C for 1-6 hours under the protection of an inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain litchi-shaped polyacrylamide microspheres. Furthermore, the polymerization reaction time is 2-4 hours; by adjusting the reaction time, not only can the production efficiency be improved, but also the formation of litchi-shaped polyacrylamide microspheres can be promoted.
[0013] In the previous work (CN118580443A), the inventor used silica of different particle sizes as reinforcing fillers and prepared polyacrylamide microspheres by dispersion polymerization, which improved the heat resistance and salt resistance of the microspheres to a certain extent. However, the microspheres have a large particle size, a relatively smooth surface, weak interaction between microspheres, and limited blocking and regulation effects. In order to improve the regulation effect of polyacrylamide microspheres, the present invention uses copper oxide quantum dots as an auxiliary agent to prepare polyacrylamide microspheres with a lychee-like morphology on the surface. Quantum dots have a smaller size, with a particle size of generally 1-10nm, which makes it easier to embed them into mesoporous microspheres. Using mesoporous microspheres as core materials, the mesoporous microspheres have a larger specific surface area and pore structure, wherein the pore structure is conducive to the embedding of copper oxide quantum dots, which is convenient for the enrichment of copper oxide quantum dots. Since the mesoporous microspheres have a large number of hydroxyl groups on their surfaces, in order to prevent them from agglomerating and improve their loading efficiency for copper oxide quantum dots, the present invention modifies them by using a mercaptosilane coupling agent, which, on the one hand, reduces the surface energy of the material and improves its dispersibility; on the other hand, the mercapto groups in the coupling agent are easily combined with the copper oxide quantum dots to prevent them from being oxidized or agglomerated, thereby improving the stability of the copper oxide quantum dots in the solvent.
[0014] The reason why copper oxide quantum dots are selected in the present invention is that compared with other metal and oxide quantum dots and quantum dots such as CdTe and ZnS, there are spatial restrictions between the electron and hole pairs in copper oxide quantum dots, which can generate additional energy. In addition, copper oxide quantum dots are monoclinic p-type semiconductors with a narrow energy band gap (1.2 eV-1.8 eV), which can effectively adsorb azo initiators, reduce the activation energy required for azo initiators to generate free radicals, accelerate the decomposition of initiators on the surface of quantum dots, and promote the formation of lychee-like morphology.
[0015] The polyacrylamide microspheres prepared by the present invention have good dispersibility and small size. They can be directly prepared from the sewage of the oil field to obtain working fluid for injection for profile control and are used in the middle and late stages of oil field development. The pore throat size of the formation is generally in the range of several hundred nanometers to several tens of micrometers. Based on this, the particle size of the synthesized polyacrylamide microspheres is adjusted and controlled. The initial particle size of the microspheres is controlled to be smaller than the diameter of the pore throats in the formation. The polyacrylamide microspheres can enter the deep part of the formation and have the characteristic of "being able to enter". After the microspheres enter the deep part of the formation, they will swell under the hydration of the surrounding water, and the particle size will continue to increase. Since the polyacrylamide microspheres themselves have a certain mechanical strength, they can block the pore throats of the formation and have the characteristic of "being able to block". The polyacrylamide microspheres are elastic and can deform and break through under a certain pressure, and then migrate to the deeper part of the formation, and gradually realize the redirection of the liquid flow step by step, and have the characteristic of "being able to move". It can be seen that the polyacrylamide microspheres prepared by the present invention have the characteristics that a deep profile control agent should have.
[0016] The microspheres prepared by the present invention have a small particle size, which can not only block large pores, but also can be continuously moved to the deep part of the formation with the injected water until it stops at the position of the low permeability layer far from the well and can no longer move, thereby blocking the low permeability layer and diverting the flow to the deep part; improving the heterogeneity between layers and within layers, expanding the volume of water injection, changing the mobility ratio between the displacement fluid and the displaced fluid, and improving the oil recovery effect. More importantly, the surface of the polyacrylamide microspheres prepared by the present invention presents a lychee-like morphology. Compared with the microspheres with smooth outer surfaces, it can not only avoid the expansion and rupture phenomenon after water absorption, but also enhance the interaction force between the microspheres, and the plugging effect is better. At the same time, as the microspheres absorb water and expand, the lychee-shaped protrusions on their surface also expand accordingly. The expanded protrusions play the role of cross-linking microspheres, which can achieve a better plugging effect.
[0017] Furthermore, in step (1), the mass ratio of the mesoporous microspheres to the mercaptosilane coupling agent is 1:(0.1-1). Furthermore, the mass ratio of the mesoporous microspheres to the mercaptosilane coupling agent is 1:(0.3-0.5). An appropriate amount of mercaptosilane coupling agent not only improves the dispersion performance of the mesoporous microspheres, but also increases the embedding rate of the quantum dots, which is conducive to the formation of a lychee-like appearance.
[0018] Furthermore, in step (1), the mercaptosilane coupling agent is at least one of 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane.
[0019] Furthermore, in step (1), the particle size of the mesoporous microspheres is 50-300 nm, and the pore size is 10-50 nm.
[0020] Furthermore, the mesoporous microspheres in step (1) are at least one of mesoporous titanium dioxide, mesoporous zirconium dioxide, mesoporous aluminum oxide, and mesoporous silicon dioxide. The rich pore structure in the mesoporous microspheres is conducive to the embedding and enrichment of copper oxide quantum dots, and the reaction rate of acrylamide monomers is faster, which is conducive to the formation of a lychee-like morphology.
[0021] Furthermore, the specific preparation process of the thiolated mesoporous microspheres in step (1) is as follows: the mesoporous microspheres and the mercaptosilane coupling agent are dispersed in a methanol solution, and then ammonia water is added as a catalyst, and the reaction is heated and stirred; after the reaction is completed, the thiolated mesoporous microspheres are obtained by centrifugation, washing, and drying; wherein the mass volume ratio of the mesoporous microspheres to ammonia water is 1 g: (0.6-1.2) mL, and the ammonia water concentration is 20 wt%; the heating reaction temperature is 55-65°C, and the reaction time is 6-8 h.
[0022] Furthermore, in step (3), the azo initiator is at least one of azobisisobutyronitrile and azobisisoheptylnitrile; the organic solvent is a mixed solution of ethanol and ethyl acetate; in step (4), the crosslinking agent is N,N-methylenebisacrylamide; and the surfactant is polyvinyl pyrrolidone.
[0023] Furthermore, the amounts of mesoporous microspheres loaded with copper oxide quantum dots, azo initiators, acrylamide, acrylic acid, crosslinking agents, and surfactants are as follows: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.1-0.8 parts of azo initiators, 10-15 parts of acrylamide, 5-10 parts of acrylic acid, 1-3 parts of crosslinking agents, and 1-3 parts of surfactants. Furthermore, the amount of azo initiators is 0.3-0.5 parts, and an appropriate amount of azo initiators can reduce the activation energy of the reaction and promote the reaction.
[0024] On the other hand, the present invention also provides the use of litchi-shaped polyacrylamide microspheres as a profile control and oil displacement agent. The polymer microspheres are a combination of polyacrylamide and quantum dot mesoporous microspheres, which not only have the expansion ability, salt resistance and deformation and plugging ability of polymer materials, but also have the size characteristics of quantum dots, thereby effectively controlling the profile of deep oil reservoirs with significant effects.
[0025] Beneficial effects:
[0026] The lychee-shaped polyacrylamide microspheres prepared by the present invention have good water absorption and swelling ability, and have excellent high temperature resistance and mineralization resistance. The polymer microspheres have excellent blocking ability. The presence of nano-microspheres in the system will promote the diffusion of the water film near the wall, reduce the oil-water interfacial tension, and enhance the miscibility of residual oil and water. In addition, the lychee-shaped polyacrylamide microspheres have a small particle size, which is smaller than the size of the formation pore throat, and can smoothly enter the deep formation, block the pore throat after absorbing water and swelling, redirect the liquid flow, expand the swept volume, and thus improve the recovery rate of crude oil. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron micrograph of the polyacrylamide microspheres prepared in Example 6;
[0028] Figure 2 This is a scanning electron microscope image of polyacrylamide microspheres prepared in Comparative Example 1;
[0029] Figure 3 A scanning electron microscope image of the polyacrylamide microspheres prepared in Example 6;
[0030] Figure 4 This is a scanning electron microscope image of the polyacrylamide microspheres prepared in Comparative Example 1. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0032] Example 1
[0033] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0034] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 7h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.3; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0035] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.01;
[0036] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0037] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 50°C for 4 hours under the protection of inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.3 part of azo initiator, 10 parts of acrylamide, 5 parts of acrylic acid, 1 part of crosslinking agent, and 1 part of surfactant.
[0038] Example 2
[0039] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0040] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 8h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.5; the mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0041] (2) adding the thiolated mesoporous microspheres to a toluene solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.1;
[0042] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0043] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 70°C for 2 hours under the protection of inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.8 part of azo initiator, 15 parts of acrylamide, 10 parts of acrylic acid, 3 parts of crosslinking agent, and 3 parts of surfactant.
[0044] Example 3
[0045] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0046] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 7h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.5; the mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0047] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.08;
[0048] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0049] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 59° C. for 3.5 hours under inert gas protection to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.4 part of azo initiator, 11 parts of acrylamide, 9 parts of acrylic acid, 1.5 parts of crosslinking agent, and 2.5 parts of surfactant.
[0050] Example 4
[0051] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0052] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.7mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 7.2h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.3; the mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0053] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.03;
[0054] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0055] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 56°C for 3.5 hours under inert gas protection to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.4 part of azo initiator, 12 parts of acrylamide, 6 parts of acrylic acid, 1.5 parts of crosslinking agent, and 1.5 parts of surfactant.
[0056] Example 5
[0057] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0058] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 63°C, and the reaction time is 8h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.4; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0059] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.07;
[0060] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0061] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 66°C for 2.5 hours under the protection of inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.5 part of azo initiator, 14 parts of acrylamide, 8 parts of acrylic acid, 2.5 parts of crosslinking agent, and 2.5 parts of surfactant.
[0062] Example 6
[0063] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0064] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 7.5h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.4; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0065] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.05;
[0066] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0067] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 60°C for 3 hours under the protection of inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.4 part of azo initiator, 12 parts of acrylamide, 8 parts of acrylic acid, 2 parts of crosslinking agent, and 2 parts of surfactant.
[0068] Example 7
[0069] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0070] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 7.5h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.1; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0071] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.05;
[0072] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0073] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 60°C for 3 hours under the protection of inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.4 part of azo initiator, 12 parts of acrylamide, 8 parts of acrylic acid, 2 parts of crosslinking agent, and 2 parts of surfactant.
[0074] Example 8
[0075] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0076] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 7.5h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:1; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0077] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.05;
[0078] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0079] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 60°C for 3 hours under the protection of inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.4 part of azo initiator, 12 parts of acrylamide, 8 parts of acrylic acid, 2 parts of crosslinking agent, and 2 parts of surfactant.
[0080] Example 9
[0081] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0082] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 7.5h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.4; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0083] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.05;
[0084] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0085] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 60°C for 1 hour under the protection of inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.4 part of azo initiator, 12 parts of acrylamide, 8 parts of acrylic acid, 2 parts of crosslinking agent, and 2 parts of surfactant.
[0086] Example 10
[0087] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0088] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 7.5h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.4; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0089] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.05;
[0090] (3) Firstly, azobisisobutyronitrile initiator is dispersed in a mixed solution of ethanol and ethyl acetate, and then mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution;
[0091] (4) Add acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agent, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 60°C for 6 hours under the protection of inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.4 part of azo initiator, 12 parts of acrylamide, 8 parts of acrylic acid, 2 parts of crosslinking agent, and 2 parts of surfactant.
[0092] Comparative Example 1
[0093] The preparation process is basically the same as that of Example 6, except that metal copper quantum dots with an average particle size of 5 nm are used to replace copper oxide quantum dots.
[0094] Comparative Example 2
[0095] A method for preparing litchi-shaped polyacrylamide microspheres comprises the following steps:
[0096] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, then adding ammonia water as a catalyst, heating and stirring to react; after the reaction is completed, centrifuging, washing and drying to obtain mercapto mesoporous microspheres; wherein the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 62°C, and the reaction time is 7.5h; the mass ratio of mesoporous microspheres and mercaptosilane coupling agent is 1:0.4; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0097] (2) adding the thiolated mesoporous microspheres to a chloroform solution of copper oxide quantum dots having an average particle size of 5 nm, uniformly dispersing the solution by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:0.05;
[0098] (3) Dispersing the mesoporous microspheres loaded with copper oxide quantum dots in a mixed solution of ethanol and ethyl acetate, stirring the mixture evenly to obtain a premixed solution;
[0099] (4) Add azobisisobutyronitrile initiator, acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinker, and polyvinyl pyrrolidone surfactant to the premixed solution and stir evenly; react at 60°C for 3 hours under inert gas protection to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres; wherein the amount of each component used in step (3) and step (4) is: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.4 part of azo initiator, 12 parts of acrylamide, 8 parts of acrylic acid, 2 parts of crosslinker, and 2 parts of surfactant.
[0100] Comparative Example 3
[0101] The preparation process is basically the same as that of Example 6, except that the mass ratio of thiol-modified mesoporous microspheres to copper oxide quantum dots is 1:0.3.
[0102] Performance Test:
[0103] The lychee-shaped polyacrylamide microspheres prepared in the above examples and comparative examples were dispersed in white oil respectively, and their initial median particle diameters D50 were measured by a laser particle size analyzer. The results are shown in Table 1.
[0104] The lychee-shaped polyacrylamide microspheres prepared in the above examples and comparative examples were dispersed in simulated formation water with a mineralization of 30,000 mg / L at 80° C. The expansion multiples at different times were measured. The results are shown in Table 1.
[0105] Low permeability cores were selected for evaluation of oil displacement effect: first, the cores were saturated with simulated formation water to determine their pore volume; then, the cores were saturated with simulated crude oil; the cores were displaced with simulated formation water until the outlet end stopped producing oil, and the recovery factor A was determined; litchi-shaped polyacrylamide microsphere dispersion was injected into the cores and placed at 65°C for 5 days; the cores were displaced with simulated formation water again until the outlet end stopped producing oil, and the recovery factor B was determined; the recovery factor increase was C (%) = (BA) / AX 100%, and the results are shown in Table 1.
[0106]
[0107] Depend on Figure 1 and Figure 3 It can be seen that the present invention has prepared lychee-shaped polyacrylamide microspheres, and the surface of the microspheres presents an arc-shaped protrusion structure similar to the surface of lychee. The formation of the above structure increases the specific surface area of the microspheres. When used in the oil displacement process, as the microspheres expand, the protrusions also gradually expand, so that an interlocking structure is formed between the balls, which promotes the plugging process. In addition, the protrusion structure disperses the stress on the surface of the microspheres during the expansion process, preventing the microspheres from rupturing. Figure 2 and Figure 4 It can be seen that the microspheres prepared using ordinary copper metal as quantum dots have a larger particle size and a smooth outer surface. This shows that ordinary copper metal quantum dots cannot form a lychee-like structure, and the oil displacement efficiency is low. This is because compared with other types of quantum dots, there are spatial restrictions between electrons and hole pairs in copper oxide quantum dots, which can generate additional energy, and it is a monoclinic p-type semiconductor with a narrow energy band gap (1.2 eV-1.8 eV), which can effectively adsorb azo initiators, reduce the activation energy required for azo initiators to produce free radicals, accelerate the decomposition of initiators on the surface of quantum dots, make the polymerization rate of polymers on the surface of mesoporous microspheres uneven, and promote the formation of lychee-like structures on the surface of polyacrylamide microspheres. Comparative Examples 2-3 show that the right amount of copper oxide quantum dots and the timing of adding materials improve the oil displacement efficiency. In comparative example 2, the azo initiator was not added in advance, which would cause polar molecules such as acrylamide and acrylic acid monomers, N,N-methylenebisacrylamide crosslinking agents to combine with copper oxide quantum dots in advance, which would not only affect the stability of the quantum dots in the solution, but also fail to enrich the initiator in the pores of the mesoporous microspheres, which is not conducive to the formation of the protruding structure. At the same time, due to the strong quantum dot effect of quantum dots, when too much copper oxide quantum dots are added, it is not only not conducive to dispersion; but also causes a large number of quantum dots to adhere to the outer surface of the mesoporous microspheres, affecting the expansion stability of the microspheres and the improvement of oil displacement efficiency.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing litchi-shaped polyacrylamide microspheres, characterized in that: The following steps are involved: (1) treating mesoporous microspheres with a mercaptosilane coupling agent to obtain mercaptolated mesoporous microspheres; the particle size of the mesoporous microspheres is 50-300 nm, and the pore size is 10-50 nm; the mesoporous microspheres are at least one of mesoporous titanium dioxide, mesoporous zirconium dioxide, mesoporous aluminum oxide, and mesoporous silicon dioxide; (2) adding thiolated mesoporous microspheres to a copper oxide quantum dot solution, uniformly dispersing by ultrasonication, and obtaining mesoporous microspheres loaded with copper oxide quantum dots after centrifugation; the mass ratio of the thiolated mesoporous microspheres to the copper oxide quantum dots is 1:(0.01-0.1); (3) Firstly, an azo initiator is dispersed in an organic solvent, and then the mesoporous microspheres loaded with copper oxide quantum dots are added and stirred evenly to obtain a premixed solution; (4) Add acrylamide and acrylic acid monomers, a crosslinking agent, and a surfactant to the premixed solution and stir evenly; react at 50-70° C. for 1-6 hours under the protection of an inert gas to obtain a reaction product mixture; centrifuge, wash, and dry the reaction product mixture to obtain lychee-shaped polyacrylamide microspheres.
2. The method for preparing litchi-shaped polyacrylamide microspheres according to claim 1, characterized in that: In step (1), the mass ratio of the mesoporous microspheres to the mercaptosilane coupling agent is 1:(0.1-1).
3. The method for preparing litchi-shaped polyacrylamide microspheres according to claim 1, characterized in that: In step (1), the mercaptosilane coupling agent is at least one of 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane.
4. The method for preparing litchi-shaped polyacrylamide microspheres according to claim 1, characterized in that: The specific preparation process of the thiolated mesoporous microspheres in step (1) is as follows: the mesoporous microspheres and the mercaptosilane coupling agent are dispersed in a methanol solution, and then ammonia water is added as a catalyst, and the reaction is heated and stirred; after the reaction is completed, the thiolated mesoporous microspheres are obtained by centrifugation, washing, and drying.
5. The method for preparing litchi-shaped polyacrylamide microspheres according to claim 1, characterized in that: In step (3), the azo initiator is at least one of azobisisobutyronitrile and azobisisoheptylnitrile; the organic solvent is a mixed solution of ethanol and ethyl acetate; in step (4), the crosslinking agent is N,N-methylenebisacrylamide; and the surfactant is polyvinyl pyrrolidone.
6. The method for preparing litchi-shaped polyacrylamide microspheres according to claim 1, characterized in that: The amounts of mesoporous microspheres loaded with copper oxide quantum dots, azo initiators, acrylamide, acrylic acid, crosslinking agents, and surfactants are respectively as follows by mass: 1 part of mesoporous microspheres loaded with copper oxide quantum dots, 0.1-0.8 parts of azo initiators, 10-15 parts of acrylamide, 5-10 parts of acrylic acid, 1-3 parts of crosslinking agents, and 1-3 parts of surfactants.
7. A litchi-shaped polyacrylamide microsphere, characterized in that: The lychee-shaped polyacrylamide microspheres are prepared by the preparation method of any one of claims 1 to 6.
8. Use of the litchi-shaped polyacrylamide microspheres as claimed in claim 7 as a profile control and oil displacement agent.
Citation Information
Patent Citations
Preparation method of core-shell type fluorescent microsphere profile control and plugging agent applied to offshore oilfield high-permeability reservoir based on quantum dots
CN115181217A
Quantum dot light-emitting film, preparation and application of quantum dot light-emitting film in white-light Mini-LED device
CN115247060A
Application of quantum dots in unconventional oil reservoir exploitation, oil-displacing agent and method for increasing yield by using oil-displacing agent
CN115306362A
High-brightness and high-stability water-soluble quantum dot fluorescent microsphere and preparation method thereof
CN117736722A
Temperature-resistant and salt-resistant polymer microsphere and preparation method thereof
CN118580443A